Augmentation of protease production from psychrotrophic Acinetobacter sp. IHB B 5011(MN12) from Western Himalayas. (October 2020) - Salwan, Richa; Sharma, Vivek; Kasana, Ramesh Chand; Gulati, Arvind
Abstract: Microbial proteases are explored for their role in food, detergent, bioremediation, pharmaceuticals, silk degumming and leather processing. Here, Acinetobacter sp. IHB B 5011 previously isolated from Western Himalayas was explored for optimization of protease production. A total of seven culture media; Basic medium (BM), Nutrient broth (NB), Gelatin broth (GB), Tryptone dextrose broth (TDB), Peptone Dextrose Broth (PDB), and Glucose Yeast extract Broth (GYB) were used. The maximum protease activity was recorded in PDB medium after 36 h. Different parameters including carbon and nitrogen source, inoculum and CaCl2 were evaluated based on Plackett-Burman design for optimum yield. The response for protease activity varied from 215-436 μg min -1 ml -1 . Further, optimization based on Central Composite Design revealed protease production with 1.4 g dextrose, 0.7 g tryptone and 0.7 g yeast extract per 50 ml medium. A significant increase in protease activity was monitored from 323 μg min -1 ml -1 to 562 μg min -1 ml -1 after optimization.